Comparison of Chemotherapeutic Regimens Frequently Used in Metastatic Non-squamous NSCLC Treatment - Krejci, Daniel; Opalka, Petr; Krejci, Jana; Zemanova, Milada; Zemanova, Petra; Kultan, Juraj; Fischer, Ondrej; Skrickova, Jana; Bratova, Monika; Cernovska, Marketa; Hrnciarik, Michal; Coupkova, Helena; et al. (Anticancer research, 2021)
BACKGROUND/AIM: Platinum-based chemotherapy with pemetrexed or paclitaxel/bevacizumab are regimens used in combination with checkpoint inhibitors in non-squamous non-small cell lung cancer (NSCLC) treatment. We conducted a real-world study to compare the outcomes of these chemotherapeutic regimens. PATIENTS AND METHODS: We investigated 1,534 patients with advanced non-squamous NSCLC treated with platin/pemetrexed (n=1212) or platin/paclitaxel/bevacizumab (n=322) in 9 cancer centres in the Czech Republic. RESULTS: The regimen containing platin/paclitaxel/bevacizumab showed significantly better overall response rate (ORR) compared to the platin/pemetrexed [40.8% vs. 32.7% (p=0.008)] in the overall population and [55.0% vs. 38.8% (p=0.002)] in the Eastern Cooperative Oncology Group performance status 0 group. There was no significant improvement in progression-free survival (PFS) and overall survival (OS) in either of these two groups of patients. CONCLUSION: In our real-world data analysis, patients treated with platin/paclitaxel/bevacizumab had better overall response rate (ORR), but not PFS or OS. Thus, both treatment regimens are similarly effective. Their selection should therefore be based on the potential side effects.
Keywords: Immune Checkpoint Inhibitors; Aged; Pemetrexed; Aged, 80 and over; metastázy nádorů; lidé středního věku; senioři; Progression-Free Survival; pemetrexed; paclitaxel; lidé; Antineoplastic Combined Chemotherapy Protocols; Middle Aged; inhibitory kontrolních bodů; Female; senioři nad 80 let; nemalobuněčný karcinom plic; protokoly protinádorové kombinované chemoterapie; ženské pohlaví; Male; doba přežití bez progrese choroby; Bevacizumab; Humans; mužské pohlaví; bevacizumab; Neoplasm Metastasis; Paclitaxel; Carcinoma, Non-Small-Cell Lung